Przywództwo jako kryterium oceny poziomu dojrzałości systemu zarządzania jakością : etap badań - Lisiecka, Krystyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The study shows the method of rating a level of quality management system maturity in a company, a new technology offered by new standard - ISO 10014:2006, which has been created for rating the influence of a level of quality management system maturity for financial and economic benefits in companies. The intention of the study was also to show the stages of research, which should verify the thesis that the higher level of quality system maturity, measured by chosen indicators, should give a company the higher level of financial and benefit indicators. In the research, carried out by TÜV NORD POLAND, leadership is indicated by respondents as third out of eight quality management rules exerting the largest influence on the level of maturity of quality management system. The company management prepares and realizes the strategy of organization, decides about the directions of development, allocates the company resources and is responsible for relations with surroundings. The business experience of every person and preliminary results of researches show that leadership exerts strong influence on the level of maturity of quality management system in an organization. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 117-127